Wheat ocs-Element Binding Factor 1 Enhances Thermotolerance by Modulating the Heat Stress Response Pathway - Samtani, Harsha; Sharma, Aishwarye; Khurana, Paramjit (Frontiers in Plant Science, 2022)
The basic leucine zipper family (bZIP) represents one of the largest families of transcription factors that play an important role in plant responses to abiotic stresses. However, their role in contributing thermotolerance in plants is not well explored. In this article, two homeologues of wheat ocs-element binding factor 1 (TaOBF1-5B and TaOBF1-5D) were found to be heat responsive TabZIP members. Their expression analysis in Indian wheat cultivars revealed their differential expression pattern and TaOBF1-5B was found to be more receptive towards heat stress. Consistent with this, the heterologous overexpression of TaOBF1-5B in Arabidopsis thaliana and Oryza sativa promoted the expression of stress responsive genes, which contributed towards thermotolerance in transgenic plants. TaOBF1-5B was seen to interact with TaHSP90 in the nucleus and TaSTI in the nucleolus and in the ER. Thus, the results suggest that TaOBF1-5B might play an important regulatory role in the heat stress response and is a major factor governing thermotolerance in plants.